Endoscopic submucosal dissection vs. endoscopic mucosal resection for early Barrett's neoplasia in the West: a retrospective study - Mejia Perez, Lady Katherine; Yang, Dennis; Draganov, Peter V.; Jawaid, Salmaan; Chak, Amitabh; Dumot, John; Alaber, Omar; Vargo, John J.; Jang, Sunguk; Mehta, Neal; Fukami, Norio; Chua, Tiffany; Gabr, Moamen; Kudaravalli, Praneeth; Aihara, Hiroyuki; Maluf-Filho, Fauze; Ngamruengphong, Saowanee; Pourmousavi Khoshknab, Milad; Bhatt, Amit (Endoscopy, 2021)
Background The difference in clinical outcomes after endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) for early Barrett's esophagus (BE) neoplasia remains unclear. We compared the recurrence/residual tissue rates, resection outcomes, and adverse events after ESD and EMR for early BE neoplasia.Methods We included patients who underwent EMR or ESD for BE-associated high grade dysplasia (HGD) or T1a esophageal adenocarcinoma (EAC) at eight academic hospitals. We compared demographic, procedural, and histologic characteristics, and follow-up data. A time-to-event analysis was performed to evaluate recurrence/residual disease and a Kaplan–Meier curve was used to compare the groups.Results 243 patients (150 EMR; 93 ESD) were included. EMR had lower en bloc (43 % vs. 89 %; P < 0.001) and R0 (56 % vs. 73 %; P = 0.01) rates than ESD. There was no difference in the rates of perforation (0.7 % vs. 0; P > 0.99), early bleeding (0.7 % vs. 1 %; P > 0.99), delayed bleeding (3.3 % vs. 2.1 %; P = 0.71), and stricture (10 % vs. 16 %; P = 0.16) between EMR and ESD. Patients with non-curative resections who underwent further therapy were excluded from the recurrence analysis. Recurrent/residual disease was 31.4 % [44/140] for EMR and 3.5 % [3/85] for ESD during a median (interquartile range) follow-up of 15.5 (6.75–30) and 8 (2–18) months, respectively. Recurrence-/residual disease-free survival was significantly higher in the ESD group. More patients required additional endoscopic resection procedures to treat recurrent/residual disease after EMR (EMR 24.2 % vs. ESD 3.5 %; P < 0.001).Conclusions ESD is safe and results in more definitive treatment of early BE neoplasia, with significantly lower recurrence/residual disease rates and less need for repeat endoscopic treatments than with EMR.